Iranian Researchers’ Contribution to Emergency Medicine During 1972-2024; A Bibliometric and Scientific Visualization Study - Salimi, Rasoul; Haseli, Davoud; Mokhtari, Heidar; Saberi, Mohammad Karim; Fattahi, Abbas; Heshmati, Bahram (Archives of Academic Emergency Medicine, 2026)
Introduction: Bibliometrics tends to analyze the scientific research items published on a specific field or topic. This study aimed to analyze Iranian researchers’ production in the field of emergency medicine (EM). Methods: This bibliometric visualization study was conducted using a descriptive-analytical approach and based on data from the Scopus database. All scientific output of Iranian researchers in the field of EM by the end of 2024 was collected and analyzed using VOSviewer 1.6.20 software. Results: Iran’s scientific output in the field of EM has grown significantly. The Archives of Academic Emergency Medicine is the top journal and Tehran University of Medical Sciences is the top institution publishing the scientific productions of Iranian researchers in the field. The United States, United Kingdom, Canada, and Australia are Iran’s largest scientific collaborating partners. Iran is the second-ranked leading country in the Middle East, publishing 20.38% of the Middle Eastern scientific publications in the field. Out of 17 countries in the Middle East, only two countries, Turkey and Iran, are in the top 20 countries in the world. The co-occurrence map of keywords showed the five thematic clusters, including risk factors and clinical outcomes, clinical symptoms and laboratory indicators, emergency and psychiatric services, medical diagnostic and imaging tools, and vital signs and clinical monitoring. Conclusion: As the second-ranked country in the Middle East and the 16th-ranked in the world, Iran has a prominent position and a high capacity for scientific development and research diplomacy in EM. The trend of scientific productions of EM in Iran is also growing. Promoting this status and maintaining this trend requires special attention from officials and policy makers to research, expanding international cooperation, increasing the quality of research and focusing on interdisciplinary and problem-oriented research.